“Where’s Wally?” Identifying theory of mind in school-based social skills interventions - O’Grady, Aneyn M.; Nag, Sonali (Frontiers in Psychology, 2022)
This mini configurative review links theory of mind (ToM) research with school-based social skills interventions to reframe theoretical understanding of ToM ability based on a conceptual mapping exercise. The review’s aim was to bridge areas of psychology and education concerned with social cognition. Research questions included: how do dependent variables (DVs) in interventions designed to enhance child social-cognitive skills map onto ToM constructs empirically validated within psychology? In which ways do these mappings reframe conceptualization of ToM ability? Thirty-one studies (conducted from 2012 to 2019) on social-cognitive skill with typically-developing children ages 3 to 11 were included as opposed to explicit ToM trainings in light of an identified performance plateau on ToM tasks in children. Intervention DVs mapped onto the following ToM constructs in at least 87% of studies: ‘Representation of Others and/or Self,’ ‘Knowledge/Awareness of Mental States,’ ‘Attributions/Explanations of Mental States,’ ‘Social Competence,’ ‘Predicting Behavior,’ and ‘Understanding Complex Social Situations.’ The absence of false-belief understanding as an intervention DV indicated a lack of direct training in ToM ability. A hierarchy to further organize the review’s ToM framework constructs as either skills or competences within the construct of ‘Representation of Others and/or Self’ is proposed. Implications for the conceptualization of ToM and social-cognitive research as well as educational practice are discussed, namely how school social skill interventions conceptualize skill along a continuum in contrast to the common artificial dichotomous assessment of ToM skill (i.e., presence or lack), yet the development of ToM can nevertheless be supported by the school environment.